2014
DOI: 10.1007/s10668-014-9556-3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental comparison of different heat transfer fluid for thermal performance of a solar cooker based on evacuated tube collector

Abstract: A comparison of thermal performance of solar cooker with two different heat transfer fluid (HTF) and effect of gate valve on discharge process of phase change material (PCM) had been investigated experimentally. In this experimental setup, solar cooker with inbuilt thermal storage unit was connected to evacuated tube collector through connecting pipes. The available solar heat in the collector was transferred to the solar cooker by natural circulation (thermosiphon) of HTF. The water and thermal oil (engine oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Solar concentrating cookers have also been used for intermediate to high-temperature applications using different test fluids [25,26,27,28,29]. However, these studies do not consider the incorporation of thermal energy storage into these cookers for off-shine cooking.…”
Section: Concentrating Solar Cookersmentioning
confidence: 99%
“…Solar concentrating cookers have also been used for intermediate to high-temperature applications using different test fluids [25,26,27,28,29]. However, these studies do not consider the incorporation of thermal energy storage into these cookers for off-shine cooking.…”
Section: Concentrating Solar Cookersmentioning
confidence: 99%
“…The figure is obtained by considering experimental results from some literatures but with idealization. The experimental results of variation of temperatures in evacuated tube solar collector can be found in the literatures (Sharma et al 2005;Peng & Chen 2009;Singh et al 2015).…”
Section: Simulation Setupmentioning
confidence: 99%
“…From their experiment, it was concluded that the late evening cooking is possible in a solar cooker with three reflectors and latent heat storage. Singh et al (2015) conducted experimental comparison of different heat transfer fluid to assess thermal performance of a solar cooker. Kanimozhi et al (2015) studied experimentally coconut oil (commercial grade) as phase change material in a box type solar cooker.…”
Section: Introductionmentioning
confidence: 99%
“…18 Kumar et al boiled 8 kg of water for 93.5 min using a cooker based on an evacuated tube solar collector 19 and tested the effect of using water and oil in heat transfer on the heat storage efficiency of a PCM and found that oil showed higher efficiency than water. 20 Farooqui tested and investigated the effect of water volumes of 3, 4, 5, 6, and 7 L and conducted that the case of a system with a fluid volume of 6 L is the most ideal, with an average energy efficiency of 21.09%. 21 El Moussaoui et al 18 developed a solar cooker that can reach 260°C under irradiance of 720 W/m² and it can maintain this temperature for 60 min in the absence of sunshine.…”
Section: Introductionmentioning
confidence: 99%